Inference of Sejahtera Academic Framework (SAF) principles in architecture pedagogy at DoA-KAED, IIUM - Asif, Nayeem; Abdullah, Fadzidah; Yusof, Zeenat Begam; Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Ismail, Mohd Noorizhar (Umut Özkaya, 2023)
Malaysia is deemed to leverage its human capital towards skillful professionals. In all fields of tertiary education, students are shaped with the foundations of digitalization, cloud computing, the Internet of Things, (IoT); Artificial Intelligent (A.I), Big Data, metaverse, autonomous robotics etc. Nevertheless, with all these emergent advancements, is there any guarantee that human value would not be jeopardized? This article infers the discourse of humanizing education, using the notion of Sejahtera Academic Framework (SAF) principles, especially on its applicability to architecture pedagogy. With the emergence of IR 4.0 advancements that overwhelms the tertiary education, a question has arisen, is there any guarantee that human value would not be jeopardized? Hence, this paper has the objective to evaluate the current pedagogic practice in architecture education in relation to the core principles and the auxiliary tools of Sejahtera Academic Framework (SAF). To achieve the objective, qualitative approach of content analysis is conducted as a strategy to inquire understanding on the subject discussed. This preliminary research is significant to ensure alignment between SAF and architecture pedagogy could be established firmly, to support the university's vision.